Community health workers' involvement in mother-child care during the 1st year after birth, in Kaya health district, Burkina Faso: A contribution analysis - Halima Tougri; Rachidatou Compaoré; Adja Mariam Ouédraogo; Blandine Bila; Marleen Temmerman; Marleen Temmerman; Séni Kouanda; Séni Kouanda (Frontiers Media S.A., 2023)
IntroductionMaternal and infant morbidity and mortality remain high in sub-Saharan Africa. However, actions to strengthen postpartum care are still weak and mainly limited to health facilities (HFs). In Kaya health district, Burkina Faso, community health workers (CHWs) were involved in mother and child care during the 1st year postpartum through home visits, outreach sessions and accompanying mothers to health facilities. The aim of this study was to assess the contribution of CHWs to postpartum women's attendance at the health facilities.MethodsWe conducted an effect assessment using Mayne and Lemire's contribution analysis framework. Qualitative and quantitative data were collected through project documents review and individual semi-structured interviews with key-informants.ResultsAll the participants interviewed acknowledged that the number of women, who came to postpartum care, had increased since the implementation of the project activities. Postpartum consultation rates within the 1st week postpartum increased from 29% in 2011 to 80% in 2015 and from 19 to 50% within 6 weeks. Others interventions such as Performance based financing, Save The Children nutritional project and the health services component of Missed Opportunities in Mother and Infant Health (MOMI) were the alternative explanations.ConclusionsCHWs involvement in women care contributed to improve their adherence to postpartum consultations in Kaya health district.